Intensive Physiotherapy in Elderly Patients: Prevention of Respiratory Complications and Optimization of Pulmonary Function (International Seven Journal of Multidisciplinary, 2023)
The aging population in intensive care units (ICUs) presents significant challenges due to the increased vulnerability of elderly patients to respiratory complications such as atelectasis and pulmonary infections. These issues arise from age-related anatomical and physiological changes that reduce lung elasticity, weaken respiratory muscles, and impair cough reflexes, exacerbating risks during critical illness. Intensive physiotherapy protocols are critical in geriatric ICUs to prevent these complications and optimize pulmonary function. These protocols typically include lung expansion techniques, airway clearance methods, early mobilization practices, and ventilatory support tailored to the unique needs of elderly patients. Evidence supports that these combined respiratory strategies reduce pulmonary complications, enhance clinical outcomes, decrease ICU length of stay, and improve functional independence. Implementing individualized physiotherapy plans within multidisciplinary teams further supports holistic recovery and better quality of life for elderly ICU patients.